Effect of Physical Therapy Cardiovasculo Pulmonal Modification (PACUM) Technique on Functional Activity, and Activity Daily Living, Among Cardiac Disease Patients (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2020)
Background. Heart disease is a leading cause of death among adults and older people in Indonesia and the world. The most affected part of hearth disease survivor life is the limitation of performing functional activities in daily life. Physical therapy cardiovascular-pulmonary modification (PACUM) technique is a method to improve physical capacity and activity of daily living (ADL) among patients of people with cardiopulmonary problems. PACUM technique is an exercise method that consists of lying down to sitting, sitting to standing, and standing to walk that aims to reduce complaints of functional activity and increase ADL of Cardiopulomary disease patients. Whether Physical therapy cardiovascular-pulmonary modification technique may affect the chest pain, and activity daily living, among cardiac disease patients is worthy of being investigated. Objective. To examine the effect of physical therapy cardiovascular-pulmonary modification technique in improving functional activity and activity daily living among cardiac disease patients. Method. This research is a quasi-experimental approach with pre and post-test time series (three times and six times) with cross over design. As many as 22 people were recruited to participate with predetermined inclusion and exclusion criteria. Physical therapy cardiovascular-pulmonary modification technique was given for two weeks, three times a week, for 20 minutes of therapy for each session. Borg Scale (BS)0-,3 and Barthel Index (BI) as the primary outcome. Results. BS and BI scores were improved significantly after the six times of physical therapy cardiovascular-pulmonary modification technique treatment, with most of the subjects achieve minimum dependent or independent. Conclusion. Physical therapy cardiovascular-pulmonary modification technique given for six times is considered as effective in improving BS and BI of people with heart disease to be more independent.